Objections to organ transplantation from brain dead donors - Olejarz, Sylwia (Current Problems of Psychiatry, 2011)
This paper does not aim to answer the question what should be done to overcome reluctance of the Japanese toward the transplantation from brain-dead donors. However, those who are waiting to learn something about reluctance toward this issue should not be disappointed. The kernel of this paper is to reveal the main objections entrenched in Japanese culture and mentality. I will strive to answer what can be learned from this example. In Japan – as elsewhere – the possibilities given by science and technology affect pa-tients’ lives and cause many dilemmas.